Ruptured Ascending Aortic Aneurysm Presenting with Hemoptysis: A Case Report (Journal of Hama University, 2026)
Aortobronchial Fistula (ABF) is uncommon but lethal if not promptly treated surgically. ABF may cause severe and lethal bleeding. It affects most often the thoracic aorta (segments 3 and 4) in patients with prior history of surgery on the thoracic vessels. Few cases in literature have been documented without prior history of thoracic surgery, trauma or aortic infectious process. ABFs rarely affect the ascending aorta and very few cases have been documented.We describe here a clinical case of a patient 70-year-old who presented with complaint of hemoptysis caused by an ABF as a complication of ruptured aortic aneurysm, affirming that investigating life threatening causes of hemoptysis is of great importance.
Keywords: Aortobronchial fistula; Hemoptysis; Ascending Aorta